Challenges In Diagnosing Systemic Lupus Erythematosus In Children: Clinical And Non-Clinical Factors - Darma, Jason Chrisandy; Hikmah, Zahrah (Faculty of Medicine, 2026)
Childhood-onset Systemic Lupus Erythematosus (cSLE) is a separate biological entity with more aggressive immunopathogenesis, faster organ damage accumulation, and greater mortality rates than adult-onset lupus. In tropical, resource-constrained environments such as Indonesia, diagnosis is routinely delayed beyond the clinically critical six-month